Mixed conifer-broadleaf trees on arbuscular mycorrhizal and ectomycorrhizal communities in rhizosphere soil of different plantation stands in the temperate zone, Northeast China - Zhang, Yong; Wang, Qingcheng; Xu, Liqing; Ma, Shuangjiao; Cui, Donghai; Zhu, Kaiyue; Feng, Wanju (Frontiers in Microbiology, 2022)
In comparison with ectomycorrhizal (EM) tree species, arbuscular mycorrhizal (AM) trees have different litter quality and nitrogen cycle modes, which may affect mycorrhizal colonization and the community composition and diversity. However, available studies addressing the mycorrhizal fungal colonization rate, diversity and community composition in mixed forest stands composed of AM and EM trees are rare. In the present study, we assessed litter quality, soil chemical properties and correlated them with mycorrhizal community characteristics in rhizosphere soils of monoculture and mixture plantation stands of AM tree (Fraxinus mandschurica Rupr.) and EM tree species (Larix gmelinii Rupr., Picea koraiensis Nakai) in Northeast China. We hypothesized that (1) the effect of mixture pattern on mycorrhizal colonization rate and diversity would change with tree species, (2). the effect of mixture pattern on mycorrhizal community composition would be less pronounced in comparison with that of tree species. We found that mixture did not change AMF colonization rate regardless of mixture identity, whereas mixture and tree species exerted significant effects on EMF colonization rate. For AMF community, both M-AS and M-AL mixture significantly increased Pielou index and Simpson index, whereas only M-AS significantly increased Sobs. For EMF community, mixture significantly affected examined diversity indices except for Chao1. Mixture significantly shifted AMF and EMF community, and the magnitude was tree species dependent. The dominant genera in AMF and EMF communities in plantation stands were Glomus and Tomentella, respectively. The EnvFit analysis showed that the determinant factors of EMF community are soil moisture, pH, nitrate nitrogen content, dissolved organic nitrogen content, soil organic matter content, soil organic carbon/total nitrogen and litter carbon/total nitrogen. In conclusion, mixed conifer-broadleaf trees significantly changed soil physcicochemical properties, litter quality as well as mycorrhizal fungi community diversity and composition.